Failure analysis of cantilever bearing in wellbore trajectory control tool with high build-up rate. (October 2019) - Sun, Qiaolei; Feng, Ding; He, Liang; Tu, Yiliu; Zhang, Hong; Shi, Lei
Abstract: A new model for mechanical analysis of the main shaft, self-aligning bearing and the cantilever bearingin wellbore trajectory control tool is presented. The theoretical model considered the effects of the parameters of the shell and the main shaft on mechanical analysis. Aiming at the problem of cantilever bearing, a finite element model (FE model) of interaction between cantilever bearing and main shaft is developed. The theoretical model and FE model are verified by experiments. The results show that, the inclination and stress concentration of the needle roller are the main reasons for the failure of the cantilever bearing. The maximum von Mises stress, deformation and inclinationare reduced by 48.62%, 66.19%, 48.09% respectively while changing the fillet radius from 0.25 mm to 0.75 mm. And the stress concentration of the needle roller and the cage in cantileverbearing can also be reduced by changing the distance between the eccentric ring and the bearings, the inner diameter of the shelland others while meeting therequirement of high build-up rate. Highlights: Presented a new theoretical model for mechanical analysis of the main shaft The influence of main shaft parameters was analyzed. Developed a finite element model to analyze the failure of cantilever bearing The fillet radius of needle roller have obvious influence on the strength of bearing. The theoretical model and the FE model were verified by experiments.